2013
DOI: 10.1242/dev.105627
|View full text |Cite
|
Sign up to set email alerts
|

ERK and phosphoinositide 3-kinase temporally coordinate different modes of actin-based motility during embryonic wound healing

Abstract: SummaryEmbryonic wound healing provides a perfect example of efficient recovery of tissue integrity and homeostasis, which is vital for survival. Tissue movement in embryonic wound healing requires two functionally distinct actin structures: a contractile actomyosin cable and actin protrusions at the leading edge. Here, we report that the discrete formation and function of these two structures is achieved by the temporal segregation of two intracellular upstream signals and distinct downstream targets. The seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 46 publications
(64 reference statements)
2
19
0
Order By: Relevance
“…Rac and Cdc42 activation, for example, is regulated by guanine‐nucleotide‐exchange factors which can be activated by PI3K‐mediated PIP 3 production and via an increase in the [Ca 2+ ] i (Benard et al ., ; Schmidt and Hall, ; Fukata et al ., ). PI3K activation could be linked to cytoskeletal reorganization, and ERK signalling regulates the actomyosin network by activation of Rho and myosin‐II (Li et al ., ). Several studies showed that different TRP channels elicit their effect on migration of stromal cells via these pathways.…”
Section: Trp Channels In Stroma Cell Migrationmentioning
confidence: 97%
“…Rac and Cdc42 activation, for example, is regulated by guanine‐nucleotide‐exchange factors which can be activated by PI3K‐mediated PIP 3 production and via an increase in the [Ca 2+ ] i (Benard et al ., ; Schmidt and Hall, ; Fukata et al ., ). PI3K activation could be linked to cytoskeletal reorganization, and ERK signalling regulates the actomyosin network by activation of Rho and myosin‐II (Li et al ., ). Several studies showed that different TRP channels elicit their effect on migration of stromal cells via these pathways.…”
Section: Trp Channels In Stroma Cell Migrationmentioning
confidence: 97%
“…Very little is known about the mechanisms that drive the propagation of Ca 2+ signaling across the epithelium, although a recent finding showed that Itpkb and its product InsP 4 , besides enhancing Rho activity and actin assembly, also facilitate Ca 2+ propagation across the epithelial tissue from the site of injury (Soto et al., ). Although it has been known from studies in other systems that both the actomyosin contraction and filopodial zippering are mechanical forces that help repair the wound (Wood et al., ), a recent study in Xenopus embryonic epithelium described a mechanism that temporally coordinates the function of these two distinct force‐generating machineries, thereby facilitating efficient embryonic wound healing (Li et al., ). This work showed that an early activation of Erk signaling initiates Rho activation and myosin‐2 phosphorylation, which in turn triggers actomyosin constriction for a quick phase of wound closure.…”
Section: Multicellular Wound Healing In Xenopus Embryosmentioning
confidence: 99%
“…This work showed that an early activation of Erk signaling initiates Rho activation and myosin‐2 phosphorylation, which in turn triggers actomyosin constriction for a quick phase of wound closure. Later on, PI3K signaling takes over, activating Rac and Cdc42, and the mode of cell motility is transformed to filopodial zippering to seal the wound edges (Li et al., ). Intriguingly, coordinated actomyosin‐based contraction also participates in the rapid neuroepithelial wound healing in the developing Xenopus brain, which expels damaged neuroepithelial cells from the brain, thereby protecting the tissue from further cell death (Herrgen, Voss, & Akerman, ).…”
Section: Multicellular Wound Healing In Xenopus Embryosmentioning
confidence: 99%
See 1 more Smart Citation
“…Use pak1-gst mRNA to detect Rac1 and Cdc42 activities; to detect RhoA activity, coinject mRNA for egfp-rhotekinGBD and rhoa ). Details of a suggested selection of plasmidsincluding pCS2-GFP/mCherry-moesin, pCS107-RhoA, pCS107-Pak1-GST, and pCS107-rGBD-GST-can be found in Li et al (2013) and Soto et al (2013). All published plasmids have been deposited in the Amaya laboratory repository and are available on request.…”
mentioning
confidence: 99%